Marking the 1918 influenza pandemic centennial: addressing regional influenza threats through the Asia Pacific Strategy for Emerging Diseases and Public Health Emergencies - Lisa Peters; Li Ailan (World Health Organization Regional Office for the Western Pacific, 2019)
In 1918, near the close of the First World War, pandemic influenza swept across the world. Spread by the movement of troops and fueled by dense military-camp living quarters, the virus caused unusually high mortality rates in people 20-40 years old. An estimated 500 million people were infected, and up to 50 million died. Since then, pandemics caused by newly emerging influenza viruses have occurred every 10-40 years, with each of the pandemics in 1957, 1968 and 1977 taking the lives of roughly one million people.1 More recently, the 2009 H1N1 influenza pandemic resulted in an estimated half a million deaths and raised concerns about how prepared the global community was to cope with future public health events.2 Past pandemics can teach us important lessons about preventing and responding to emerging global health threats. This special issue highlights significant achievements across the Western Pacific Region in global pandemic preparedness and response.